CHARACTER BUILDING DAN PENDIDIKAN ISLAM DI ERA NEW NORMAL - Mohammad Makinuddin; Saeful Anam; Shoffiyah Shoffiyah (MIYAH : Jurnal Studi Islam, 2020)
Abstract: This article aims to describe how to build character in children in the new normal era. This article is conceptually written as a medium for providing information to educators, parents and people involved in the distance learning process (PJJ) that is currently being used. Online system learning has increased digital use considerably, so awareness of the negative effects of digital technology needs to be increased. Character building is expected to minimize the negative effects of digital. The formation of a generation with character is part of the aspired national education goals. In line with that, Islamic education also aims at building the morals (character) of all human beings. In addition, the presence of educators is also important in order to achieve this noble goal. Even though the pandemic limits the face-to-face space, educators must be present to continue their mission. Between educators, parents, and students, there must be synergy as part of efforts to build national character. The final hope is that Islamic education in the midst of digital flow will become the best defense and lead them to grow into a digital generation with quality (character).Keywords: Character Building, Islamic Education, New Normal